2021
DOI: 10.1093/rheumatology/keab544
|View full text |Cite
|
Sign up to set email alerts
|

Age at onset in axial spondyloarthritis around the world: data from the Assessment in SpondyloArthritis international Society Peripheral Involvement in Spondyloarthritis study

Abstract: Objectives Age at onset is useful in identifying chronic back patients at an increased risk of axial spondyloarthritis (axSpA). Yet, the majority of data on which the age at onset <45 years criterion was based originates from Europe. Therefore, it is unknown if this criterion applies in other parts of the world. We aimed to assess age at onset of axSpA and its relationship with HLA-B27 and gender across the world. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
(38 reference statements)
2
11
0
Order By: Relevance
“…starting in patients' mid-20s, 5 axSpA has a significant and lasting impact on patient lives [6][7][8] and a high disease burden. 3 Many patients with axSpA fail treatment, do not achieve treatment targets or experience residual symptoms, [9][10][11] demonstrating the need for more treatment options with novel modes of action.…”
Section: Spondyloarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…starting in patients' mid-20s, 5 axSpA has a significant and lasting impact on patient lives [6][7][8] and a high disease burden. 3 Many patients with axSpA fail treatment, do not achieve treatment targets or experience residual symptoms, [9][10][11] demonstrating the need for more treatment options with novel modes of action.…”
Section: Spondyloarthritismentioning
confidence: 99%
“… 1–3 The axSpA spectrum encompasses patients with definitive structural damage to the SIJ visible on plain radiographs (radiographic (r-)axSpA, also known as ankylosing spondylitis 4 ), and patients without definite radiographic sacroiliitis (non-radiographic (nr-)axSpA). Typically starting in patients’ mid-20s, 5 axSpA has a significant and lasting impact on patient lives 6–8 and a high disease burden. 3 Many patients with axSpA fail treatment, do not achieve treatment targets or experience residual symptoms, 9–11 demonstrating the need for more treatment options with novel modes of action.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, 92% of patients with AS were less than 45 years old at disease onset. 34 The mean age of the PsA subjects in this study was 41 years old. Research by Deike et al, showed that most cases of PsA began at 50-59 years old.…”
Section: Resultsmentioning
confidence: 93%
“…The predominance of AxSpA diagnoses in females within the current study, contrasts previous research describing bias towards perceived prevalence of AxSpA in males among health professionals, although the latter represented the cohort majority (Redeker et al., 2019). Variation in characteristics between males and females diagnosed with AxSpA has been identified in the literature, with the former being associated with earlier onset of disease (Boel et al., 2022). This was consistent in the current cohort where men had an age at symptom onset (39.6 ± 10.3) 3.7 years earlier than women (43.3 ± 10.8 years).…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: AFC, Agenda for Change; APP, Advanced Practice Physiotherapist; EHSC, Edinburgh Health and Social Care Partnership; MSK, Musculoskeletal; WTE, Whole Time Equivelant.960 -HEPBURN T A B L E 2 HEPBURN -961AS(Boel et al, 2022). Whilst details of the care journeys preceding APP consultation were not available, this may potentially represent missed opportunities for earlier AxSpA diagnosis within the current cohort reported in previous studies given the association between positive radiological findings and disease progression -despite the shorter time to diagnosis recorded compared to the UK nationalT A B L E 2 (Continued)present favourable conditions for early detection of AxSpA and reducing diagnostic delay.…”
mentioning
confidence: 99%